SENSORY ATTENUATION ASSESSED BY SENSORY EVOKED POTENTIALS IN FUNCTIONAL MOVEMENT DISORDERS. Issue 9 (13th August 2015) - Macerollo, A; Chen, JC; Parees, I; Kassavetis, P; Kilner, J; Edwards, MJ
Abstract : Objective: Functional (psychogenic) movement disorders (FMD) have features associated with voluntary movement (e.g. distractibility) but patients report movements to be out of their control. One explanation for this phenomenon is that sense of agency for movement is impaired. The phenomena of reduction in the intensity of sensory experience when movement is self-generated and a reduction in sensory evoked potentials (SEPs) amplitude at the onset of self-paced movement (sensory attenuation) have been linked to sense of agency for movement. Here, we report the results of a study examining suppression of sensory evoked potentials (SEPs) at the onset of self-generated movements in healthy participants and FMD patients. We hypothesised that patients with FMD would have less SEPs suppression at the onset of movement compared to healthy controls. Method: Seventeen patients with FMD affecting body parts excluding upper limbs were recruited from outpatient clinics at The National Hospital for Neurology and Neurosurgery, Queen Square, London, UK. They had documented or clinically established FMD following Fahn and Williams criteria. Patients with sensory abnormalities were excluded. Seventeen healthy volunteers matched with respect of gender, age and handedness were studied as the control group. We compared amplitude of SEPs from median nerve stimulation at rest and at the onset of a self-paced movement of the thumb in both groups. Results: Patients showed lack of attenuation of SEPs at the onset of movement compared to reduction in amplitude of SEPs in controls. Indeed, FMD patients had significantly different ratios of movement onset to rest SEPs than did healthy controls in each electrode: 0.79 in healthy controls and 1.35 in patients at F3 (p<0.001, t=−4.22), 0.78 in healthy controls and 1.12 in patients at C3 (p=0.004, t=−3.15) and 0.77 in healthy controls and 1.05 in patients at P3 (t=−2.88, p=0.007). Conclusion: Patients with FMD have reduced sensory attenuation as measured by SEPs at onset of self-paced movement. This finding can be plausibly linked to impairment of sense of agency for movement in these patients. The measurement of sensory attenuation in this relatively simple paradigm is an interesting candidate biomarker for FMD which could be explored in future work.